Hollow-core fibres for temperature-insensitive fibre optics and its demonstration in an Optoelectronic oscillator. Issue 1 (December 2018) - Mutugala, U.; Numkam Fokoua, E.; Chen, Y.; Bradley, T.; Sandoghchi, S.; Jasion, G.; Curtis, R.; Petrovich, M.; Poletti, F.; Richardson, D.; Slavík, R.
Abstract Many scientific and practical applications require the propagation time through cables to be well defined and known, e.g., an error in the evaluation of signal propagation time in the OPERA experiment in 2011 initially erroneously concluded that Neutrinos are faster than light. In fact, there are many other physical infrastructures such as synchrotrons, particle accelerators, telescope arrays and phase arrayed antennae that also rely on precise time synchronization. Time synchronization is also of importance in new practical applications like autonomous manufacturing (e.g., synchronization of assembly line robots) and upcoming 5G networks. Even when the propagation time through a coaxial cable or optical fibre is carefully calibrated, it is affected by changes in the ambient temperature, posing a serious technological challenge. We show how hollow-core optical fibres can address this issue.